2021
DOI: 10.1016/j.psj.2021.101214
|View full text |Cite
|
Sign up to set email alerts
|

Buffered formic acid and a monoglyceride blend coordinately alleviate subclinical necrotic enteritis impact in broiler chickens

Abstract: The objective of this study was to evaluate the effect of 2 different doses of a partially buffered formic acid product (Amasil NA; 61% formic acid, 20.5% sodium formate), and a monoglyceride blend of short- and medium-chain fatty acids (BalanGut LS P) on necrotic enteritis ( NE ) infected broilers in terms of performance, intestinal microbial population and short-chain fatty acids concentrations in the gastrointestinal tract. A total of 528-day-old as hatched Ross 308 broilers were allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 47 publications
3
15
1
Order By: Relevance
“…However, the results observed in this study also revealed that the dietary addition of FA in grower and finisher phases did not have positive impacts on performance and intestinal health over the diet supplemented with MG only in the starter phase as indicated by similar BWG, FCR, intestinal lesions, apparent ileal digestibility, bacterial quantification, and gene expression results in birds fed both additive supplemented diets under the present conditions. Similar to our results, a recent study reported that birds supplemented with FA (high dose) had no effects on performance and mortality in birds under sub-clinical NE challenge [18]. Cumulatively, the findings of this study indicated the beneficial effects of additive MG in reducing the severity of clinical NE on intestinal health, evidenced by improved immunity, gut integrity, digestibility, and reduced mortality.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…However, the results observed in this study also revealed that the dietary addition of FA in grower and finisher phases did not have positive impacts on performance and intestinal health over the diet supplemented with MG only in the starter phase as indicated by similar BWG, FCR, intestinal lesions, apparent ileal digestibility, bacterial quantification, and gene expression results in birds fed both additive supplemented diets under the present conditions. Similar to our results, a recent study reported that birds supplemented with FA (high dose) had no effects on performance and mortality in birds under sub-clinical NE challenge [18]. Cumulatively, the findings of this study indicated the beneficial effects of additive MG in reducing the severity of clinical NE on intestinal health, evidenced by improved immunity, gut integrity, digestibility, and reduced mortality.…”
Section: Discussionsupporting
confidence: 90%
“…Due to the nature of clinical NE present in the current study, the NC group had much higher mortality and thus the entire experimental period showed mostly the performance of survived birds, whose performance was quickly recovered, thus less performance effects of OA were detectable following the recovery. Similar to our results, birds fed blended OA had no effects on BWG but improved FCR under a clinical NE challenge [46] and subclinical NE challenge condition [18]. Moreover, Geier et al [46] also reported the high mortality in OA-fed birds and not inconsistent from the control group, which is inconsistent with our findings.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations